A fiery & furious people: a history of violence in England - Sharpe, J. A. (Random House Books, 2016)
Professor James Sharpe explores the brutal underside of our national life across some seven centuries. And as he looks at the litany of assaults, murders and riots that pepper our history he traces the subtle shifts both in the nature of violence and in people's attitudes to it